2008
DOI: 10.1007/s11695-008-9631-7
|View full text |Cite
|
Sign up to set email alerts
|

Limb Contouring after Massive Weight Loss: Functional Rather than Aesthetic Improvement

Abstract: The rate of complications in limb contouring after weight loss is higher than the analogue esthetic procedures. Nevertheless, due to the rehabilitative significance of limb surgery after weight loss, this step is to be included as fundamental in obese patients' surgical therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…When performing post-bariatric surgery in massive weight-loss patients, the surgeon is most often aiming for functional improvement in the first line and aesthetic improvement in the second line as has been mentioned by Bruschi et al 13 We agree with Wolf et al who, as bariatric surgeons, reflect that dermolipectomies are one more step in the treatment of the morbidly obese patient, and bariatric surgeons must take care of them as an integral part of the management of their obesity. 14 Fraccalvieri et al and Breiting et al reported that postbariatric patients have a significantly higher risk of developing complications after abdominoplasty, including wound infection and dehiscence, than non-postbariatric patients.…”
Section: Discussionmentioning
confidence: 62%
“…When performing post-bariatric surgery in massive weight-loss patients, the surgeon is most often aiming for functional improvement in the first line and aesthetic improvement in the second line as has been mentioned by Bruschi et al 13 We agree with Wolf et al who, as bariatric surgeons, reflect that dermolipectomies are one more step in the treatment of the morbidly obese patient, and bariatric surgeons must take care of them as an integral part of the management of their obesity. 14 Fraccalvieri et al and Breiting et al reported that postbariatric patients have a significantly higher risk of developing complications after abdominoplasty, including wound infection and dehiscence, than non-postbariatric patients.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, surgery for these reasons must be considered to be reconstructive rather than cosmetic. 28 We showed that the majority of post-bariatric surgery patients present physical discomfort, often in several body areas, particularly in the abdomen, upper arm, rear/ buttock and chest/breast. We found a significant association between female sex, the amount of weight loss and difference in BMI with physical unpleasantness due to the surplus skin.…”
Section: Discussionmentioning
confidence: 84%
“…Figure 15.1 shows the hypogastrium, flanks and lateral aspects of the chest, which are common areas of liposuction in the trunk. Limb contouring is an important aesthetic procedure in massive weight loss patients (Bruschi et al, 2009). Fat accumulates in the inferior aspect of the proximal upper limb, often referred to as 'bingo wings'.…”
Section: Anatomy and Areas Of Considerationmentioning
confidence: 99%